2003
DOI: 10.1177/082585970301900303
|View full text |Cite
|
Sign up to set email alerts
|

A Good Death in Rural Kenya? Listening to Meru Patients and Their Families Talk about Care Needs at the End of Life

Abstract: What constitutes a good death in sub-Saharan Africa? In Meru District in Eastern Kenya, we listened to 32 patients with ongoing cancer or AIDS, and to their carers as they talked about end-of-life experiences and care needs. Patients described how the support of close family relationships, and the care shown by their community and religious fellowships helped meet many of their emotional, social, and spiritual needs. But physical needs often went unmet. Patients died in pain. Some suffered in poverty, others w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
124
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(128 citation statements)
references
References 11 publications
(6 reference statements)
3
124
0
Order By: Relevance
“…Twenty patients were recruited to represent the local demography of lung cancer with respect to age, sex, and methods of treatment. In Kenya, also as part of a larger study,10 hospital doctors identified 32 adult patients with a life limiting illness who were at different stages of the disease progression. We purposively sampled participants to give an even mix of those being cared for at home and those receiving most of their care in hospital.…”
Section: Methodsmentioning
confidence: 99%
“…Twenty patients were recruited to represent the local demography of lung cancer with respect to age, sex, and methods of treatment. In Kenya, also as part of a larger study,10 hospital doctors identified 32 adult patients with a life limiting illness who were at different stages of the disease progression. We purposively sampled participants to give an even mix of those being cared for at home and those receiving most of their care in hospital.…”
Section: Methodsmentioning
confidence: 99%
“…Articles were excluded if they did not pertain to adults, were from a non-Western culture, 28,29 were historical reviews of the time prior to 1995, or dealt solely with euthanasia or assisted suicide. Abstracts of the 84 remaining articles were reviewed to determine the type of article, the perspective, and the year of publication.…”
Section: Sample Selectionmentioning
confidence: 99%
“…Accepting death as ‘a path we all must tread’ provides space for families and patients to talk about dying 16. In some societies beliefs about the contaminating effect of the dead and the fear of breaking bad news need to be addressed.…”
Section: Challenges Now Facing Palliative Care In Africa and Potentiamentioning
confidence: 99%